Daytime ion and electron temperatures in the topside ionosphere at middle latitudes. Issue 2 (6th February 2017) - Hsu, Chih‐Te; Heelis, Roderick A.
Abstract: In the topside ionosphere during the daytime, the thermal electrons are directly heated by photoelectron fluxes from the local and conjugate hemispheres. The heat is lost primarily through conduction to the regions below where collisions with the ions provide the cooling. Ions are heated by collisions with both the electrons and ions and are cooled primarily by conduction to lower altitudes where the heat is lost to collisions with the neutral gas. Here we examine the effects of ion composition on the ion and electron temperatures in the midlatitude topside ionosphere during daytime using data from the Defense Meteorological Satellite Program F15 satellite in 2004–2006. The variations of electron and ion temperature with plasma density and composition indicate how the heat is exchanged between the different constituent ions and the role played by the solar zenith angle and the solar ionizing flux ( F 10.7 ). The observations show that the daytime temperature difference between the O + and electron is smallest when the fractional contribution of H + is the highest. In such an environment the electrons transfer heat to the H + then to the O + through ion‐ion collisions. Key Points: The topside plasma temperature, number density, and composition are primarily dependent on solar zenith angle H + provides an intermediate thermal coupling between the electrons and O + O + temperature is closer to the electron temperature when H + is present